METODOLOGI PENELITIAN TINDAKAN KELAS: SOLUSI PRAKTIS BAGI GURU SEKOLAH DASAR - Nurhaswinda Winda; Rindani Nur Adma Rinda; Chintya Mutiara Chintya; Laila Pajriani Laila; Suci Akfiza Rahmadani Suci; Suci Rahmadani Suci (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Classroom Action Research (CAR) is a systematic approach that enables teachers to identify, analyze, and solve instructional problems directly in the classroom. This article discusses the CAR methodology as a practical solution for elementary school teachers in improving the quality of learning. Through a cycle of planning, action, observation, and reflection, CAR encourages teachers to become researchers in their own classrooms, allowing them to implement more effective teaching strategies that meet students' needs. By understanding and applying the CAR methodology, teachers can enhance their professionalism and student learning outcomes in a sustainable way.